Influencia de la suplementación de hierro oral (chis-paz) en los niveles de hemoglobina de los niños de 3 y 4 años de la unidad educativa “San José” del barrio “San Antonio” de Tena. año 2015 - ESCOBAR CARRASCO, ADRIANA KARINA (2016)
The purpose of the study was to understand the “influence of the supplementation of oral iron (Chis-Paz) on hemoglobin levels in children aged 3 and 4 years from the “San José School in Tena’s “San Antonio” neighborhood. The design was: longitudinal, application, descriptive, bibliographic and field. Blood tests were 74 mothers were also interviewed to obtain relevant information on the demographic and socio-economic characteristics of the research subjects. Following the administration of the Chis-Paz, the levels of hemoglobin were compared. The most relevant results showed male children at 62.12% and female children at 37.88%; the predominant age group corresponded to 4-year-olds with 59.46% and 3-year-olds at 40.54%; the predominate ethnic group was the indigenous at 64.86% and mestizos with 35.15%. 20.27% of the children presented with low hemoglobin levels prior to supplementation with iron (Chis-Paz); 6.76% of the children registered at these levels post supplementation with iron. The nursing intervention plan consisted of the taking of pre-supplementation blood samples, educational activities, the delivery of oral iron (Chis Paz), and taking post supplementation blood samples. In conclusion, the study demonstrated that the supplementation of iron (Chis-Paz) had a positive influence on the hemoglobin levels of the child subjects of the investigation that contributed to overcoming the statistics of anemia presented at the beginning of the investigation.